Surgical treatment of patients with descending purulent mediastinitis - Shevchuk, I.M.; Snizhko, S.S. (Medicni Perspektivi, 2021)
The aim of the study was to improve the results of treatment of patients with descending purulent mediastinitis by means of individualized surgical tactics with the priority use of minimally invasive surgical interventions and developed methods of drainage of the mediastinum and pleural cavity. Examination and treatment of 73 patients with descending purulent mediastinitis receiving treatment in the department of thoracic surgery of Ivano-Frankivsk regional clinical hospital was carried out. Treatment of patients in the main group included intramediastinal administration of antibiotics, the use of the developed method of cascade drainage of the mediastinum and pleural cavity, the priority use of video-assisted thoracoscopy and surgical tactics aimed at anticipating the spread of the purulent process in the mediastinum. The rapid and reliable decrease in the indices of endogenous intoxication in the main group confirms the effectiveness of the developed tactics of surgical treatment of patients with mediastinitis, adequate sanation of purulent mediastinatis, complete removal of the purulent substrate from the mediastinum and pleural cavity. The developed tactics of surgical treatment of purulent mediastinitis allowed reducing the overall postoperative mortality from 26.3% in the comparison group to 11.4% in the main group of patients.